Ultra-processed food consumption and children and adolescents' health - Samantha Bittencourt Mescoloto; Gabriela Pongiluppi; Semíramis Martins Álvares Domene (Elsevier, 2024)
Objectives: To present observational studies investigating associations between the consumption of ultra-processed foods and health outcomes in childhood and adolescence. Data source: Observational, cross-sectional, or longitudinal studies were considered, and identified in the Scopus, Web of Science, Pubmed and Scielo databases, without date restrictions. Data synthesis: The most frequent combinations of risk factors in children and adolescents involved an unhealthy diet, with regular consumption of ultra-processed foods to the detriment of a diet based on fresh or minimally-processed foods and insufficient levels of physical activity; records on alcohol and tobacco use were identified. Combined, these practices contribute to the findings that indicate an increase in the prevalence of obesity in children and adolescents and a sedentary lifestyle, with a decrease in physical activity, in addition to representing a risk for the development of chronic non-communicable diseases, such as cardiovascular diseases and periodontal disease in childhood and adolescence. Conclusions: The present study maps the current literature on the topic and indicates the direction of the approach for health promotion and prevention of NCDs in children and adolescents. Among the different risk factors that negatively affect the full development of this population, frequently eating breakfast and practicing physical activity is most strongly associated with a lower consumption of ultra-processed foods and should be part of an integrated approach to promoting eating practices that favor the reduction of diseases also in adult life.